Evaluating the effect of intraoperative peritoneal lavage on bacterial culture in dogs with suspected septic peritonitis - Swayne, Seanna L. (Canadian Veterinary Medical Association, 2012)
This pilot study describes the effect of intraoperative peritoneal lavage (IOPL) on bacterial counts and outcome in clinical cases of septic peritonitis. Intraoperative samples were cultured before and after IOPL. Thirty-three dogs with presumed septic peritonitis on the basis of cytology were managed surgically during the study period. Positive pre-lavage bacterial cultures were found in 14 cases, 13 of which were a result of intestinal leakage. The post-lavage cultures showed fewer isolates in 9 cases and in 1 case became negative. The number of dogs with a decrease in the concentration of bacteria cultured from pre-lavage to post-lavage samples was not statistically significant. There was no significant effect of the change in pre- to post-lavage culture, single versus multiple types of bacteria, selection of an appropriate empiric antimicrobial on survival or the need for subsequent surgery.